Raphael Rabello e Odeon de Ernesto Nazareth: interpretação, arranjo e improvisação - Alvimar Liberato Nunes (2007)
Essay about brazilian guitar player Raphael Rabello's (1962-1995) approach to Odeon (1910), a landmark choro by brazilian composer and pianist Ernesto Nazareth (1863-1934), departing from a comparison among (1) the original edition for piano, (2) commercial and non-commercial audio and video recordings by Raphael Rabello and (3) a classical transcription for guitar by Antônio Sinópoli. We recurred to the concept of Representation of the Original Instance by ARAGÃO (2001) to explain the processes of arrangement and improvisation. We referred to ALMEIDA (1999), and SANTOS (2001) on stylistic aspects; to CHEDIAK (1986) regarding improvisation; and to ZANON (2004) regarding technical issues of the guitar. The appendix includes transcriptions of the arrangements and improvisation in the recordings.